The Montreal cognitive assessment is superior to national institute of neurological disease and stroke-Canadian stroke network 5-minute protocol in predicting vascular cognitive impairment at 1year - Dong Y.H. (BioMed Central Ltd., 2018)
10.1186/s12883-016-0570-y